Anhedonia and depression severity measures during ketamine administration in treatment-resistant depression - Kwaśny, Aleksander; Cubała, Wiesław Jerzy; Włodarczyk, Adam (Frontiers in Psychiatry, 2024)
Background: Anhedonia is a core symptom of depression characterized by a diminished ability to experience pleasure. Currently available treatments for depression often fall short in adequately addressing anhedonia that often presents as a chronic and debilitating symptom. Ketamine is known to possess antianhedonic properties. Methods: This post-hoc analysis of a naturalistic observational study of treatment-resistant depression inpatients (n=28) analyzed antianhedonic response patterns measured by Snaith-Hamilton Pleasure Scale and changes in Inventory of Depressive Symptomatology in responders (n=6) and non-responders (n=22) stratified per Montgomery-Åsberg Depression Rating Scale during short-term ketamine treatment. Results: Results show that responders significantly improve in anhedonia over time (p=0.0084) and at the 7th infusion and follow-up (both p<0.05). Non-responders reported significant reduction in anhedonia over time (p=0.0011) and at the 5th, 7th infusion and at the follow-up (all p's<0.05). Non-responders were also observed to improve significantly in self-reported depression at the 7th infusion (p=0.0219) but not at the follow-up. Discussion: There is no complete overlap between change in depressive symptoms and anhedonia. Therefore, it might be assumed ketamine alleviates anhedonia as an individual symptom domain regardless of formal treatment outcome.